The Effectiveness of Various Essential Oils on the Market as Aedes Aegypti Mosquito Repellent - Army Mitasari; Aris Santjaka; Iqbal Ardiansyah (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: In Indonesia, the average dengue cases are 121,191 each year with a Case Fatality Rate (CFR) of 0.69%. Mosquito control with common chemical methods will negatively impact the environment and human health and can cause mosquitoes to develop resistance. Environmentally-friendly replacement chemicals derived from plants such as citronella contains 16.27% citronella and 19.88% geraniol. In addition, lavender plants also contain 35% alcohol comprising linalool and geraniol as well as other chemicals such as borneol. Furthermore, 8-20% of camphor and borneol in rosemary can also be a natural mosquito repellent ingredient. Methods: This study is a True Experiment with The Posttest-Only Controlled Group Design. The number of Aedes aegypti mosquitoes used for each treatment was 20. The study subjects were divided into 4 groups comprising 0.4 ppm of citronella, lavender, and rosemary essential oils and aquades as control. Replication was carried out 3 times and observations were conducted for 20 minutes. Results and Discussion: The Anova Factorial test resulted in a p-value of â‰¤ 0.05. In addition, there was a significant difference in the number of Aedes aegypti mosquitoes expelled from humidifier vapor. Furthermore, the Least Significant Difference (LSD) test showed that citronella essential oil was most effective in repelling mosquitoes because it has a p-value of â‰¤ 0.05 and largest average difference between other essential oils. Conclusion: Essential oils from citronella are most effective and stable for 30 seconds to 20 minutes to repel mosquitoes compared to lavender and rosemary essential oils